The type series of Pseudopaludicola ternetzi Miranda-Ribeiro, 1937 (Anura, Leiuperidae) with designation of a lectotype - Caramaschi, Ulisses; Pombal Jr., José P. (Zootaxa, 2011)
The genus Pseudopaludicola was erected by Miranda-Ribeiro (1926) to accomodate one species, P. falcipes (Hensel, 1867). Posteriorly, he added a second species to the genus, P. ternetzi, based on an undefined number of specimens, but surely involving males and females (Miranda-Ribeiro 1937). After a relatively detailed description and figures of a male and a female specimen, he particularly standed out one female specimen as coming from “Goyaz (Dr. Ternetz). Passa-Tres”. Paulo Miranda-Ribeiro (1955), in his survey on the types of the species described by his father, cited P. ternetzi, but he did not define a type specimen for the species. Notwithstanding, Frost (2011) referred to purportedly “Syntypes: MNRJ (2 specimens); MNRJ 488, considered holotype by Miranda-Ribeiro, 1955”, but this latter is actually the holotype of Barycholos ternetzi (Miranda-Ribeiro, 1937) (see Caramaschi & Pombal 2001). The type locality was cited by Frost (2011) only as “Goyaz [= Goiás]”, following P. Miranda-Ribeiro (1955), but adding that it was “restricted to ‘Passa Três, Goiás’ by Bokermann (1966). Actually, Bokermann (1966)”, besides incorrectly having synonymized the species with Pseudopaludicola ameghini (Cope, 1887) (see Lobo 1994), just referred, as type locality for the species, without comments, the only locality cited by Miranda-Ribeiro (1937) for one specimen examined by him. Given that for ongoing taxonomic revisions it is important to precisely identify all name-bearing type specimens in this genus, we examined the type series of P. ternetzi. Herein we designate a lectotype and list the paralectotypes for the species, thereby restricting and defining its type locality.